Dumbbell-Shaped Epidural Capillary Hemangioma Presenting as a Lung Mass. Issue 14 (15th July 2015) - García-Pallero, María A.; Torres, Cristina V.; García-Navarrete, Eduardo; Gordillo, Carlos; Delgado, Juan; Penanes, Juan R.; García-Campos, María T.; Sola, R. G.
<x xml:space="preserve">Abstract</x> Study Design. A case report and literature review. Objective. We present the fourth case of a spinal epidural capillary hemangioma with a dumbbell-shaped appearance in the magnetic resonance image reported in the literature and the second presented as a lung mass. Summary of Background Data. Hemangiomas are congenital vascular malformations that pathologists frequently consider to be hamartomatous malformations. Hemangiomas of the spine are usually lesions of the vertebral bodies, but they can sit in other locations such as the intramedullary or epidural space. Purely epidural hemangiomas are rare and most of them are of cavernous type. Methods. We present a 67-year-old female with a thoracic dumbbell-shaped capillary hemangioma with both foraminal and intrathoracic extensions, whose presentation was pleural effusion associated with mediastinal mass suggestive of pulmonary neoplasia. Surgical treatment consisted of total removal en bloc of the lesion. Results. Microscopic evaluation showed a fibrofatty tissue with a proliferation of vascular structures that were generally of a small size, with areas of myxoid appearance. To date, there have been 8 epidural capillary hemangiomas of the thoracic and lumbar spine reported in the literature, and only 3 of them were dumbbell-shaped with extraforaminal extension. Conclusion. It is important to consider the diagnosis of hemangiomas in the differential diagnosis of epidural lesions with dumbbell-shaped appearance in the magnetic resonance image, especially at the thoracic level. It is a benign and potentially curable disease and the most appropriate surgical treatment is en bloc resection of the entire lesion. They are usually presented as a progressive myelopathy, so early treatment may prevent permanent neurological deficits. Level of Evidence: 5